2019
DOI: 10.1080/15548627.2019.1632122
|View full text |Cite
|
Sign up to set email alerts
|

SNX10 (sorting nexin 10) inhibits colorectal cancer initiation and progression by controlling autophagic degradation of SRC

Abstract: The non-receptor tyrosine kinase SRC is a key mediator of cellular protumorigenic signals. SRC is aberrantly over-expressed and activated in more than 80% of colorectal cancer (CRC) patients, therefore regulation of its stability and activity is essential. Here, we report a significant down regulation of SNX10 (sorting nexin 10) in human CRC tissues, which is closely related to tumor differentiation, TNM stage, lymph node metastasis and survival period. SNX10 deficiency in normal and neoplastic colorectal epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 41 publications
0
41
1
Order By: Relevance
“…mRNAs play an important regulatory role in numerous biological processes, tumorigenesis, and development (20). Recent publications have revealed that SNX10 (21) and SMAD4 (22) act as tumor suppressors in CRC and could be potential therapeutic targets. CP1 (23) and ANG2 (24) were associated with promoting tumor progression and metastasis and may be useful targets for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…mRNAs play an important regulatory role in numerous biological processes, tumorigenesis, and development (20). Recent publications have revealed that SNX10 (21) and SMAD4 (22) act as tumor suppressors in CRC and could be potential therapeutic targets. CP1 (23) and ANG2 (24) were associated with promoting tumor progression and metastasis and may be useful targets for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, SRC gene copy number in stage IV CRC has been associated with left sided-tumours and liver metastases [ 59 , 60 ]. SFKs upregulation may also involve miRNA epigenetic mechanisms [ 50 ], such as mi-129-1-3p downregulation [ 62 ], and aberrant SFK protein accumulation, that can be induced by inactivation of the ubiquitination factor Casitas B-lineage lymphoma proto-oncogene (Cbl) or inhibition [ 63 ] of Src autophagic degradation through SNX10 inactivation [ 64 ].…”
Section: Sfks In Human Crcmentioning
confidence: 99%
“…The STAT-3 dimer translocates into the nucleus and promotes the transcription of downstream genes. STAT-3, signal transducer and activator of transcription-3; JAK, Janus kinase; c-Myc, MYC proto-oncogene bhLh transcription factor; Bcl-xL, BCL2-like 1; Bcl-2, BCL2 apoptosis regulator; VEGF, vascular endothelial growth factor; PIAS, protein inhibitors of activated STATs; SOCS, suppressors of cytokine signaling.STAT-3 in normal and neoplastic colorectal epithelial cells and tumor tissues with upregulated Src(74). Src homology region 2 domain-containing phosphatase 1 (ShP-1) is a non-receptor protein tyrosine phosphatase and serves as a tumor suppressor gene in numerous cancer types.…”
mentioning
confidence: 99%